2022
DOI: 10.1371/journal.pone.0274845
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the kinetics and magnitude of antibody responses to different SARS-CoV-2 proteins in Sinopharm/BBIBP-CorV vaccinees following the BNT162b2 booster or natural infection

Abstract: The kinetics and magnitude of antibody responses to different proteins of the SARS-CoV-2 virus in Sinopharm/BBIBP-CorV vaccinees has not been previously studied. Therefore, we investigated antibody responses to different SARS-CoV-2 proteins at 2 weeks, 3 months, and 6 months post-second dose in previously infected (n = 20) and uninfected (n = 20) Sinopharm/BBIBP-CorV vaccinees. The IgG antibodies to the S, S1 and S2 and N were several folds higher in those who had natural infection compared to uninfected indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Moreover, consistent with a previous report [23], the recipients of the RNA vaccines (Pfizer and Moderna) had higher peak antibody titers than the viral-vector and alum-adjuvanted inactivated-vaccine recipients. In line with previous studies, our results showed that after the initial peak, the IgGs antibodies dropped to lower levels, quite quickly, for up to 3 months, for inactivated and viral vector vaccines [22,40,41], and more progressively for RNA vaccines, at up to 7 months after immunization [22,24,28].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, consistent with a previous report [23], the recipients of the RNA vaccines (Pfizer and Moderna) had higher peak antibody titers than the viral-vector and alum-adjuvanted inactivated-vaccine recipients. In line with previous studies, our results showed that after the initial peak, the IgGs antibodies dropped to lower levels, quite quickly, for up to 3 months, for inactivated and viral vector vaccines [22,40,41], and more progressively for RNA vaccines, at up to 7 months after immunization [22,24,28].…”
Section: Discussionsupporting
confidence: 93%
“…The population assessed was placed in the frontline and was supposed to have one of the highest seroprevalences reported due to natural infection. Interestingly, one study comparing naive, alpha/delta/omicron infected, and BNT boosted among two-dose BBIBP demonstrated that a previous infection with any strain provided humoral immune protection as good as BNT booter [35] , [50] . Additionally, longer intervals (seven to eight months) between the second and booster dose were associated with high anti-SARS-CoV-2 IgG antibody levels [17] , [22] , [34] , consistent with our results.…”
Section: Discussionmentioning
confidence: 99%